Coaching Cadres in Posyandu Management in Ranah Singkuang Village, Kampar Regency - Fitri, Fitri; Lailiyana, Lailiyana; Hernitati, Hernitati (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2023)
The implementation of convergence action through cadre coaching at posyandu activities is very important for early detection of child growth and development. Posyandu can be the main vehicle for improving stunting prevention education. The implementation of posyandu activities is carried out with a 5-table system, namely registration, height and weight measurement, recording, nutrition counseling, and health services. The purpose of this service activity is to provide training to cadres to increase the knowledge and skills of cadres in managing posyandu. The method in this activity is to provide training to cadres in the form of book media. This activity was attended by 12 cadres. The understanding of the material provided is about posyandu management in the 5 tables system which includes weighing and measuring toddlers, calculating the age of toddlers, and plotting on KMS. Measurement indicators using pre and post-test questionnaires. The results showed that pre-test, as many as 8.3% of cadres' knowledge was good, 75%, the cadres had sufficient knowledge and as many as 16.7% had less knowledge. The results of the cadres' posttest, as many as 16.7% of cadres' knowledge became good, 83.3% had sufficient knowledge. The knowledge of the cadres has been improved, because based on the results of the post-test the level of knowledge of the cadres is no longer lacking regarding management in the posyandu.